Pronouns in Embedded Contexts at the Syntax-Semantics Interface (Studies in Linguistics and Philosophy,, 2018)
This volume presents studies on pronouns in embedded contexts, and offers fundamental insights into this central area of research. Much of the recent research on pronouns has shown that embedded environments, such as clausal complements of attitude predicates, provide a window into the nature of pronouns. Pronouns in such environments not only exhibit familiar distinctions such as that between bound and referential pronouns; if they refer to the attitude holder, they also participate in a broader range of phenomena, e.g., distinguishing between a de se reading (involving a conscious self-directed belief) and a de re reading (involving an accidental belief about oneself). Topics covered in the book include: the semantics of attitude reports that contain pronominal elements, the semantics of pronominal features and their connection to indexicality, new insights in the connection of pronominal typology and logophoricity or anti-logophoricity, and finally, the localization of embedded pronouns within a bigger picture involving the nature of perspective and the analysis of quasi-pronominal phenomena such as sequence of tense.